2017
DOI: 10.1891/0886-6708.vv-d-16-00045
|View full text |Cite
|
Sign up to set email alerts
|

Victim Alcohol Intoxication During a Sexual Assault: Relations With Subsequent PTSD Symptoms

Abstract: This study examines associations between women’s alcohol intoxication at the time of sexual assault and posttraumatic stress disorder (PTSD) symptoms. Drawing on the dual representation theory (Brewin, Gregory, Lipton, & Burgess, 2010), we hypothesized that intoxication at the time of assault would be positively associated with both overall symptoms of PTSD and PTSD re-experiencing symptoms in particular. A total of 143 community women (ages 18 to 26; 71.3% European American) reporting sexual victimization com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 42 publications
0
22
1
Order By: Relevance
“…These findings also shed light on the overall associations between alcohol-involved SA and subsequent intrusive memories. Prior studies examining alcohol involvement during SA and subsequent PTSD-related intrusions have revealed mixed findings (Aakvaag et al, 2018;Brown et al, 2009;Jaffe et al, 2017;Littleton et al, 2009;Peter-Hagene & Ullman, 2018;Zinzow et al, 2010), and we found no difference by SA type in overall intrusion symptoms. However, intrusions after alcohol-involved SA depended on daily consumption of alcohol in our study, which suggests that post-SA alcohol use may be an important factor not considered in previous work.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…These findings also shed light on the overall associations between alcohol-involved SA and subsequent intrusive memories. Prior studies examining alcohol involvement during SA and subsequent PTSD-related intrusions have revealed mixed findings (Aakvaag et al, 2018;Brown et al, 2009;Jaffe et al, 2017;Littleton et al, 2009;Peter-Hagene & Ullman, 2018;Zinzow et al, 2010), and we found no difference by SA type in overall intrusion symptoms. However, intrusions after alcohol-involved SA depended on daily consumption of alcohol in our study, which suggests that post-SA alcohol use may be an important factor not considered in previous work.…”
Section: Discussioncontrasting
confidence: 56%
“…Compared to non-alcohol-involved SA, some have found that alcohol-involved SA is associated with less severe PTSD symptoms (Peter-Hagene & Ullman, 2018), including fewer initial intrusive symptoms , whereas others indicate no differences (Aakvaag, Strøm, & Thoresen, 2018;Brown, Testa, & Messman-Moore, 2009;Littleton, Grills-Taquechel, & Axsom, 2009;Zinzow et al, 2010). Over time, however, alcohol-involved assault survivors report more persistent PTSD intrusive symptoms than non-alcohol assault survivors , especially when there is greater intoxication at the time of the SA (Jaffe et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The studies examining the effects of acute substance intoxication varied in their designs: four studies compared PTSD symptoms in assault victims with and without acute substance intoxication ( 41 , 62 , 63 , 70 ); five studies categorized sexual assault experiences into types and compared their unique effects on PTSD symptoms ( 64 68 ); two studies identified subgroups of victims based on reported sexual assault characteristics and compared these subgroups with one another to investigate effects of these characteristics on PTSD symptoms ( 61 , 69 ). Due to the advantages of longitudinal over cross-sectional studies in more effectively examining the effect of pre-assault substance consumption on the development, and especially the course, of PTSD symptoms, longitudinal studies are given more weight and hence are presented in advance of cross-sectional studies in this review.…”
Section: Resultsmentioning
confidence: 99%
“…Participants were drawn from a larger, multiwave, multisite study of emotion dysregulation and sexual revictimization (also see Jaffe et al, 2017;Watkins, Franz, DiLillo, Gratz, & Messman-Moore, 2015;Watkins et al, 2014). A total of 491 women between 18 and 25 years of age were recruited from the community at four sites in the United States (Lincoln and Omaha, Nebraska; Jackson, Mississippi; Oxford, Ohio) for a study of women's life experiences.…”
Section: Participantsmentioning
confidence: 99%